(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
The atom-bond connectivity (ABC) index of a graph G is a connectivity topological index was defined as Â where dv denotes the degree of vertex v of G. In 2010, M. Ghorbani et. al. introduced a new version of atom-bond connectivity index as Â where Â In this paper, we compute a cloused formula of ABC4 index of an infinite class of Nanostar Dendrimer D3[n]. A Dendrimer is an artificially manufactured or synthesized molecule built up from branched units called monomers.